Pengaruh Model Pembelajaran Learning Cycle dan Problem Based Learning terhadap Hasil Belajar Siswa pada Materi Ekosistem - Masni Veronika Situmorang (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This research was conducted in class 7th SMP Swasta Methodist Pematangsiantar which aims to determine: The effect of learning model (Learning Cycle, Problem Based Learning, and Konvensional) on student’s learning outcomes in ecosystem material. The population in this study amounted four classes and otherwise being research sample was as much as three classes, 7th-A as class with Problem Based Learning, 7th- B as class with Learning Cycle, and 7th-C as class with Konvensional. The data collection instrument by using: Test student’s learning outcomes in the form of the 30 multiple-choice items. This research method is quasi experiment with data analysis technique using Anacova Test and Anova 2 lines with a significance level α = 0,05. The result of this research found that: There is an effect of learning model (Learning Cycle, Problem Based Learning, and Konvensional) on student’s learning outcomes in ecosystem material, where a group of student who learned wih Learning Cycle 74,95±11,386, Problem Based Learning 81,33±10,23, and Konvensional 68,19±10,24, with Fcount = 13,280; p = 0,000 and significance level α = 0,05.